Using quantitative methodologies to conduct a systematic review in social sciences: Proknowk-C and Ordinatio Method in the theme “Financialization in Corporate Governance” - Vieira, R. (2022)
The work presented here arises in the context of a larger work, which is related to the need of carrying out a survey of possible gaps in the literature on the subject of financialization within the scope of Corporate Governance, followed by a Systematic Review of the topic. Thus, using the Vos Viewer tool and two scientific methodologies, that have gained prominence in recent years - ProKnow-C Method and Ordinatio Methodi - a set of protocols based on bibliometric indexes (number of citations, age of the article and journal impact factor) was initiated in order to define the final base portfolio for the intended systematic review that would lead to the identification of gaps in the literature and thus identify possible new lines of research. The purpose of this paper is not at all to present the empirical results and gaps that the systematic review itself allowed to identify, but rather to present the methodology used for the construction of the systematic review carried out a posteriori.